iSalic - 25% methyl salicylate ointment, 3% camphor and 3% menthol - Mohamed, Farahidah; Chatterjee, Bappaditya (2020)
Label displaying the brand name 'iSalic' and main ingredients i.e 25% methyl salicylate, 3% camphor, 3% menthol and ointment bases, with other instruction and labelling as required by regulatory.